Caribbean Report 15-01-1997 - Orr, Carol (anchor); Lue, Richard (interviewee); Smith, Lou (correspondent); Bayley, Hugh (interviewee); Richards, Ken (correspondent); Sealy, Andrew (interviewee); Singh, Doodnauth (interviewee) (The British Broadcasting Corporation, 1997)
Reports that the US Federal Aviation Authority has failed to give Jamaica’s aviation body a Category I rating has been denied by the Jamaican government. How this lowered category ties in with scheduled services to the Eastern Caribbean is also discussed. Next, the Caribbean Conference of Churches in Grenada is calling for the release of Phyllis Coard and Colville McBarnett currently serving life sentences for the 1983 murder of Prime Minister Maurice Bishop. Their medical conditions are deteriorating. Next, the preparations for elections in Guyana are discussed. The preparations are falling behind. In the next segment, Labour MP, Hugh Bayley, has begun an attempt today to change the rules of the British Overseas Aids budget. In the 1980’s aid was linked with arms sales to Malaysia, however, the Labour MP believes that aid should be targeted solely at the world’s poorer countries. Next, stories of Caribbean interest appearing in the British press are featured. Lastly, fast bowlers Kenneth Benjamin and Nixon McClean are replaced by Phil Simmons and Cameron Cuffy in the West Indies cricket tour to Australia.
1. Headlines (00:00-00:28)
2. Reports of a category II rating for Jamaica's Federal Aviation Authority. Richard Lue, Airlines Sales Director is interviewed (00:32-03:27)
3. Caribbean Conference of Churches in Grenada is calling for the release of Colville McBarnett and Phyllis Coard. Lou Smith reports from St. Georges (03:28-05:52)
4. Elections due in Guyana in October. Deonath Singh, Guyana's Election Commissioner is interviewed (05:56-09:29)
Keywords: Elections- Guyana.; Cricket -- West Indies.; Federal Aviation Authority -- United States.; Aviation -- Jamaica.; Air Jamaica.; Conference of Churches -- Grenada.; Bishop, Maurice.; Coard, Phyllis.; McBarnett, Colville.; British Overseas Aids.